Laparoscopic management of colo-colonic intussusception, an uncommon cause of acute intestinal obstruction in adult: a case report - Singh, Amit; Ali, Shadan; Raj, Supriya; Aggrawal, Lalit; Mohta, Anup (International Surgery Journal, 2024)
Colo-colonic intussusception is an uncommon cause of acute intestinal obstruction in adults. Traditionally open surgical methods were chosen as the primary form of treatment; however, few recent reports of successful treatment have been achieved with laparoscopic approach. We report a 44-year-old lady, who presented to accident and emergency department of our hospital with features of acute intestinal obstruction for two days. Ultrasonography and Contrast-enhanced computed tomography (CECT) of abdomen revealed colo-colonic intussusception. After resuscitation and optimization, patient underwent diagnostic laparoscopy which confirmed colo-colonic intussusception involving splenic flexure and proximal descending colon. Laparoscopic classical left hemicolectomy with stapled side to side colo-colonic anastomosis was done. Post-operative course was uneventful. Histopathology report confirmed presence of intraluminal hyper plastic polyp as lead point.